2013
DOI: 10.4103/0970-4388.121816
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physio-chemical properties of saliva and comparison of its relation with dental caries

Abstract: The physio-chemical properties of saliva like pH, buffering capacity, salivary flow rate, concentration of various components like proteins, calcium and antioxidant defense system play a major role in the development of caries. Hence, more clinical and laboratory studies are needed to determine the exact relationship between these physio-chemical properties of saliva and dental caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
3
8
0
1
Order By: Relevance
“…In the present study, the mean BCSS at baseline was 9.58, which increased to 9.71 postdiet counseling, found to be statistically nonsignificant. This finding is in accordance with several studies 7 22 28 which concluded that there is a weak correlation between the buffering capacity and caries activity. Our study was in contrast to the study conducted by Ericsson, 30 which showed that the salivary buffering capacity has a negative relationship with caries incidence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the mean BCSS at baseline was 9.58, which increased to 9.71 postdiet counseling, found to be statistically nonsignificant. This finding is in accordance with several studies 7 22 28 which concluded that there is a weak correlation between the buffering capacity and caries activity. Our study was in contrast to the study conducted by Ericsson, 30 which showed that the salivary buffering capacity has a negative relationship with caries incidence.…”
Section: Discussionsupporting
confidence: 93%
“…27 In the present study, the mean resting pH prior to diet counseling in caries-active individuals was found to be 7.05, which increased to 7.08 postdiet counseling, which was not statistically significant. This finding was in correlation with the study conducted by Dogra et al 28 and Wu et al, 26 which stated that caries-active children had a mean resting pH of 7.20 and 7.17 respectively. Preethi et al 7 evaluated the mean resting pH of saliva in caries-free and caries-active children as 7.18 and 7.15 respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Analogues results were reported previously (35,36)where resting salivary ow rate was increased highly signi cantly in CF individuals. It was also like the other observations where the results of various studies showed that alterations in saliva properties play an essential role in protection against dental caries (37)(38)(39).…”
Section: Discussionsupporting
confidence: 82%
“…Dogra ve ark. 7-14 yaş grubu çocuklarda tükürük pH'ının çürük diş sayısı çok olan çocuklarda, çürük dişi olmayanlara göre daha düşük olduğunu, ancak istatistiksel olarak anlamlı bir sonuç bulamadıklarını belirtmişlerdir (22). Benzer şekilde Prabhakar ve ark.…”
Section: Discussionunclassified